The exploitation of old-age pensioners by micro-lenders in rural areas of the Greater Giyani Municipality - Ndlovu, Samson Madala (My University, 2007)
Micro-lending has long been a controversial issue. Although old-age pensioners are excited about the opportunity of accessing credit from micro-lenders, some are exploited. The aim of the study was to investigate how old-age pensioners fall prey for micro-lenders, who charge them high interest on small short-term loans. The exploratory design was used for this investigation because it would provide the researcher with an in-depth understanding of old-age pensioners’ experiences when dealing with micro-lenders. The study is based on a case study of the three villages, Mphagani, Zava, and Khashane (MZK), in the rural areas of Greater Giyani Municipality, Limpopo province. Most old persons are reliant on social grants to support themselves and their extended families. Sometimes they need to supplement their income because of the responsibilities that they have in their families. Micro-finance institutions are targeting women because they are likely to be more reliable as borrowers and increased income is more likely to accrue to the family and especially children. The results of the study show that majority of old-age pensioners take loans from micro-lenders. The reasons for borrowing micro loans are categorized into four major needs for money: purchase of food, payment for health-care services, funerals, and education. These micro-lenders are not compliant with the rules and procedures of the National Credit Act.
Thesis (M.Dev.) --University of Limpopo, 2007
Keywords: Pensioners; Micro-lenders; 305.24; Aged -- South Africa -- abuse of; Loans, Personal -- South Africa